If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2y = 6x + 7y Solving 3x + 2y = 6x + 7y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 3x + -6x + 2y = 6x + -6x + 7y Combine like terms: 3x + -6x = -3x -3x + 2y = 6x + -6x + 7y Combine like terms: 6x + -6x = 0 -3x + 2y = 0 + 7y -3x + 2y = 7y Add '-2y' to each side of the equation. -3x + 2y + -2y = 7y + -2y Combine like terms: 2y + -2y = 0 -3x + 0 = 7y + -2y -3x = 7y + -2y Combine like terms: 7y + -2y = 5y -3x = 5y Divide each side by '-3'. x = -1.666666667y Simplifying x = -1.666666667y
| 3=-15c+8 | | 6-4x=11-5x+2x | | 4(2m-3)=5m+6+3m+6 | | 2x^4-2x^3+3x^2+2x-2=0 | | 18+49m=74 | | 3x^3-5x^2+10x+9=2 | | 2(x+3)=-4x-30 | | 3x^3-5x^2+10x+9=5 | | (-11+2i)-(7-8i)=0 | | 11+19= | | 15x-16=14x | | -9(12-12x)=-9(12+5x)+3x | | -5x+17=-33x | | 14+4x=43 | | 12x+5y+7y-3x= | | 5x-22=2x-4 | | -35x-7y=56 | | 2x-6+5x+3=46 | | A(3x+8)=-18x+b | | 40x=41x-2 | | 3x+17=4x | | -c=-22 | | 3+1=4x+1 | | 3x^3-5x^2+10x+9= | | q-11=9 | | 33x+-4=95 | | 3+1=7y+2 | | 2w+3-4w=17-(3w+2) | | 3+1=7y-2 | | 3=-12c+7 | | 3+1=7y-9 | | 15t-11t= |